0
0
Cho `a^2 + b^2 + c^2 = a^3 + b^3 + c^3 = 1` . Tính `S = a^2 + b^2012 + c^2012`
Hãy luôn nhớ cảm ơn và vote 5*
nếu câu trả lời hữu ích nhé!
5204
4872
`a^2 + b^2 + c^2 = a^3 + b^3 + c^3 = 1`
`=> (a^3 + b^3 + c^3) - (a^2 + b^2 + c^2) =0`
`a^3 - a^2 + b^3 - b^2 + c^3 - c^2 = 0`
`a^2(a-1) + b^2(b-1) + c^2(c-1) =0 (1)`
Do `a^2 + b^2 + c^2 = 1`
Mà `a^2 >=0 AA a, b^2 >=0 AA b, c^2 >=0 AA c`
`=> {(a^2 <=1, b^2 <=1, c^2 <=1):}`
`=> {(a<=1),(b<=1),(c<=1):}`
`=> {(a-1<=0),(b-1<=0),(c-1<=0):}`
Mà `a^2>=0 AA a, b^2>=0AA b, c^2 >=0 AA c`
`=> {(a^2(a-1) <=0),(b^2(b-1) <=0),(c^2(c-1) <=0):}`
`=> a^2(a-1) + b^2(b-1) + c^2(c-1) <=0 (2)`
Từ `(1)` và `(2)`
`=> a^2(a-1) = b^2(b-1) = c^2(c-1) =0 `
`=> {([(a=0),(a=1):}),([(b=0),(b=1):}),([(c=0),(c=1):}):}`
Kết hợp với `a^2 + b^2 + c^2 = a^3 + b^3 +c^3 = 1`
`=> [( {(a=b=0),(c=1):} ), ( {(a=1),(b=c=0):} ), ( {(a=c=0),(b=1):} ) :}`
`+) TH1 : a =b = 0` và `c = 1=>S = 0^2 + 0^2012 + 1^2012 = 1`
`+) TH2: a = 1` và `b = c = 0 => S = 1^2 + 0^2012 + 0^2012 = 1`
`+) TH3: a =c = 0` và `b = 1 => S = 0^2 + 1^2012 + 0^2012 = 1`
Vậy `S=1`
Hãy giúp mọi người biết câu trả lời này thế nào?
Bảng tin